Seismic Performance and Vibration Control of Rapid Construction Environmental Protection Wall Based on Artificial Intelligence - Jie Fu; Shuangxi Zhou; Li Liu; Mingxing Liu (International Transactions on Electrical Energy Systems)
With the continuous increase in building types, people's demand for buildings is increasing. In addition to focusing on the work of the building itself, high requirements are also placed on the safety, stability, and durability of the building. Especially in other earthquake-prone areas, it is even more necessary to strengthen seismic isolation research to reduce vibration. Rapid construction of environmental protection walls pays attention to environmental protection and efficiency during construction, which can effectively solve problems in the construction process, but the seismic resistance of rapid construction environmental protection walls is unknown. Therefore, this paper used artificial intelligence technology to study the seismic performance of rapid construction environmental protection walls and analyzed its vibration control. This paper firstly established the seismic performance analysis model of the environmental protection wall, used the finite element method to construct the environmental protection wall model, and then used the artificial intelligence algorithm to analyze the seismic performance of the rapid construction environmental protection wall. The experimental results showed that the peak load of the rapid construction environmental protection wall was about 250 KN, and the seismic performance was good.